International and Cross Border Entrepreneurship: The Case of Greece and Bulgaria - Ioannis Katsikis; Garyfallos Fragidis; Dimitrios Paschaloudis (European Regional Science Association (ERSA), 2012)
Although neighboring countries and both members of the EU, Greece and Bulgaria have very different social and economic environments in which entrepreneurial activities take place. At the same time, there are strong entrepreneurial ties between private firms of the two countries, initiated by organizations how see those different environments as opportunities to further develop their business by operating across the borders. This fact has result to a large number of private and public firms, mainly from the Greek side, that have moved their operations in Bulgaria as well as to many Bulgarian citizens who commute to the Greek side looking for work. Although this phenomenon has been well descripted in the literature, the research on understanding the actual reasons is only minimal. In this paper, we map the entrepreneurial and investment activities between the two countries in order to better understand cross-border activities of the firms. In order to do so, we use quantitative data covering both entrepreneurial activities, such as joint ventures and the direct investments between the two countries in an effort to understand the direction, the spatial concentration and the sectoral dissemination of the entrepreneurial activities undertaken. We analyze data relevant to the existing cross border entrepreneurial activities and their orientation and both quantitative and qualitative information for the firms, joint ventures, public - private partnerships and other forms of formal collaborations. Our analysis provides interesting results for the specific organizations, the conditions and targets for which they choose to cross the borders. Furthermore, our research sheds light on the competences and the competitive advantages those firms try to gain. Based on those results, our paper concludes by providing insights on the regional and organizational strategies for the internationalization and the development of bilateral collaboration between the organizations of the two countries that could contribute positively in responding to the current economic crisis in Greece.
Keywords: L26; F23; F21; 330; cross border cooperation; international entrepreneurship; Greece; Bulgaria